Respon Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) Terhadap Tingkat Dosis Pupuk Kotoran Kambing dan Frekuensi Penyiraman - Riani, Alifia; Ritawati, Sri; Rohmawati, Imas; Lizansari, Kirana N (JURNAL BUDIDAYA PERTANIAN, 2025)
Vegetable crops are one of the horticultural commodities with a great opportunity to be developed, because of their relatively high nutritional contents. The production of pakcoy plants in Indonesia experienced fluctuation from 2021 as much as 727,467 tons, which increased in 2022 to 760,608 tons and decreased in 2023 to 686,876 tons. One of the efforts to optimize pakcoy production is to optimize photosynthesis product, because plants need sufficient organic matter and water. This research aimed to determine the growth and yield response of pakcoy plants to the level of goat manure fertilizer dosage and watering frequency. This research was conducted in a home garden in Pandeglang, Banten. The research used a factorial Randomized Block Design (RBD) consisting of two factors. The first factor was the level of goat manure fertilizer dosage (P) which consisted of three levels, namely 157 g/polybag (P1), 189 g/polybag (P2), 220 g/polybag (P3). The second factor was the frequency of watering (F) which consisted of four levels, namely watering once a day (F1), watering twice a day (F2), watering once every two days (F3), watering twice every two days (F4). The results showed that the dosage level of goat manure fertilizer 157 g/polybag (P1) or equivalent to 50 tons/ha gave the highest effect on the variables of plant height and leaf length. The treatment of watering frequency twice a day (F2) showed a significant effect on the variable of plant height, plant fresh weight, root fresh weight, plant marketable weight and root dry weight.